2021
DOI: 10.1177/1099636221993848
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the mechanisms of damage in foam core sandwich composites under impact loading and low temperatures

Abstract: Recent interest in Arctic exploration has brought new challenges concerning the mechanical behavior of lightweight materials for offshore structures. Exposure to seawater and cold temperatures are known to degrade the mechanical properties of several materials, thus, compromising the safety of personnel and structures. This study aims to investigate the low-velocity impact behavior of woven carbon/vinyl ester sandwich composites with Polyvinyl chloride (PVC) foam core at low temperatures for marine application… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The compact specimen exhibited a sharper drop in the post-peak regime, which indicates higher damage as higher energy is dissipated over a short global deformation (Figure 16a). Open curves without rebound can be seen for all tests, indicating the complete penetration and perforation of both types of samples [63,64].…”
Section: Mechanical Response From Impact Testsmentioning
confidence: 80%
See 1 more Smart Citation
“…The compact specimen exhibited a sharper drop in the post-peak regime, which indicates higher damage as higher energy is dissipated over a short global deformation (Figure 16a). Open curves without rebound can be seen for all tests, indicating the complete penetration and perforation of both types of samples [63,64].…”
Section: Mechanical Response From Impact Testsmentioning
confidence: 80%
“…Based on the force-displacement responses, the equivalent impac stiffness was 222 N/mm and 310 N/mm for foamed and compact parts, respectively. The compact specimen exhibited a sharper drop in the post-peak regime, which indicate higher damage as higher energy is dissipated over a short global deformation (Figure 16a) Open curves without rebound can be seen for all tests, indicating the complete penetration and perforation of both types of samples [63,64]. Average tanδ values of 0.0391 and 0.0394 were found for foamed and compact conditions, respectively, over the tested frequency range.…”
Section: Mechanical Response From Impact Testsmentioning
confidence: 95%
“…These results were later confirmed by Castellanos and Prabhakar. 5 While the aforementioned studies addressed foam-core sandwich panel behavior, there has been very little research concerning the low temperature behavior of Divinycell foams specifically. In some recent experiments, 6 we found that Divinycell H-foams undergo a ductile-to-brittle transition when temperatures are around À50°C.…”
Section: Introductionmentioning
confidence: 99%